Molecularly engineered CMC-caged PNIPAM for broadband light management in energy-saving window. (1st April 2022) - Liu, Yang; Chen, Qunfeng; Liu, Gengmei; Tao, Tao; Sun, Haodong; Lin, Zhenhui; Chen, Lihui; Miao, Qingxian; Li, Jianguo
Abstract: Dynamic transparent-opaque transition behavior endows the stimuli-chromic materials with the solar modulation capability. However, these materials commonly involve the high manufacturing cost and complexity, the additional consumption of electric energy for solar modulation, or the weak effectiveness of light management. Herein, we develop a low-cost yet broadband light management sodium carboxymethyl cellulose-caging-poly(N-isopropylacrylamide) thermochromic composite (i.e., CMC/PNIPAM), where the nanoscale-skeleton CMC molecules well cage the PNIPAM molecules, which enables the homogeneous dispersion and sufficient distribution of the PNIPAM nanogels in the system. The CMC/PNIPAM features the excellent solar-modulation capability (including optical transmittance modulation of 68.17% and infrared transmittance modulation of 48.50%) and a low phase temperature of 30 °C, as well as the long-term stability of dynamic transparent-opaque transition. Such merits of the broadband light management, low cost, simply fabrication as well as scaling up, make the CMC/PNIPAM function as a promising candidate for the energy-saving buildings and construction. Graphical abstract: Unlabelled Image